The potential of Biogas in Energy Transition in Indonesia. Issue 1 (April 2021) - Rianawati, Elisabeth; Sagala, Saut; Hafiz, Ichsan; Anhorn, Johannes; Alemu, Sinshaw; Hilbert, Jorge; Rosslee, Dwight; Mohammed, Mutala; Salie, Yaseen; Rutz, Dominik; Rohrer, Michael; Sainz, Angela; et al.
Abstract: Indonesia is an agrarian country that has a rich bioenergy potency in liquid (biodiesel, bioethanol). The Government of Indonesia (GoI) has set the target to achieve 23% of renewable energy utilization into the national energy mix by 2025. In addition, the GoI also aims to increase the production of biofuel to 7.21 million kilolitres by 2019. Theoretically, biogas technology will be a strategic measure in achieving the target, however, at the moment the biogas technology market in Indonesia is still in a nascent state, especially for the direct utilization of biogas for electricity production. Alternatively, biogas provides Indonesia with a promising source of energy, which can be injected directly into natural gas grids and hitchhike existing distribution infrastructure, resulting in reduced costs along the production-distribution pipeline. For this reason, biomethane has been the focus of some developing countries (e.g Argentina, Republic of South Africa) in moving toward energy transition. This paper examines the state of the biogas market in Indonesia using literature review. The status of natural gas is mapped out through its available potential and the existing initiation of national programs related to biogas. Finally, the study provides recommendations on how biogas technology could accelerate the energy transition in Indonesia.